2020
DOI: 10.1103/physrevlett.124.101302
|View full text |Cite
|
Sign up to set email alerts
|

Probing Primordial Chirality with Galaxy Spins

Abstract: Chiral symmetry is maximally violated in weak interactions [1], and such microscopic asymmetries in the early Universe might leave observable imprints on astrophysical scales without violating the cosmological principle. In this Letter, we propose a helicity measurement to detect primordial chiral violation. We point out that observations of halo-galaxy angular momentum directions (spins), which are frozen in during the galaxy formation process, provide a fossil chiral observable. From the clustering mode of l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 39 publications
2
43
0
Order By: Relevance
“…Such an explanation is valid only in the linear regime, namely in the limit where density perturbations are small with respect to the mean and where flows are laminar. As a collapsing region reaches turnaround, tidal torques cease to be effective and the final angular momentum of a collapsed region is far from what tidal torque theory would predict [9][10][11] . Although one recent study 12 has demonstrated that galaxy spin direction (that is, clockwise versus anticlockwise) can be predicted from initial conditions, revealing a critical clue to the nonlinear acquisition of angular momentum, our understanding of spin magnitude, direction and history remains in its infancy.…”
mentioning
confidence: 94%
“…Such an explanation is valid only in the linear regime, namely in the limit where density perturbations are small with respect to the mean and where flows are laminar. As a collapsing region reaches turnaround, tidal torques cease to be effective and the final angular momentum of a collapsed region is far from what tidal torque theory would predict [9][10][11] . Although one recent study 12 has demonstrated that galaxy spin direction (that is, clockwise versus anticlockwise) can be predicted from initial conditions, revealing a critical clue to the nonlinear acquisition of angular momentum, our understanding of spin magnitude, direction and history remains in its infancy.…”
mentioning
confidence: 94%
“…Although the spins of dark matter halos are not directly observable, hydrodynamic galaxy formation simulations all suggest that the spins of central galaxies and the spins of their host halos are highly correlated (e.g., [6] and references therein). In Lagrangian space, by using the E-mode reconstructed density fields [7] we are able to construct a scale dependent spin mode, and successfully predict the spins of dark matter halos [8]. By applying this method to the ELUCID reconstruction of the local universe [9] and a first spin catalog of observed galaxies, [10] for the first time confirmed the correlation between galaxy spins and initial conditions of the Universe.…”
Section: Introductionmentioning
confidence: 74%
“…However, since I ij can not be obtained from the first principal, we are more interested in a predictable spin field given an initial density reconstruction. In [8] we construct a spin field from a "tidetide" self-interaction L TT ¼ ϵ ijk T r jl T R lk where r and R are two smoothing scales smoothed on the tidal tensor. Choosing Gaussian smoothing kernels with R → r þ , the spin reconstruction can be approximated by…”
Section: Spin Conservation and Reconstructionmentioning
confidence: 99%
See 1 more Smart Citation
“…From past and current N -body simulations, the spin correlation between halos and their Lagrangian protohalos (e.g. [14,17,26] and this work) is higher than 0.6, meaning that the nonlinear effects at low redshifts only add less than factor of 2 scatter to the spin correlation. Recent galaxies formation simulations (e.g.…”
Section: Discussionmentioning
confidence: 68%